The Anesthesiologist Workforce in 2013 A Final Briefing to the American Society of Anesthesiologists - Baird, Matthew (RAND Corporation, 2014)
Important changes are taking place in the health care sector that have implications for future supply and demand of anesthesiologists. To determine the implications for the anesthesiologist workforce, RAND Corporation researchers conducted a national survey of American Society of Anesthesiologists members in 2013. This report documents findings by region, gender, and other provider and facility characteristics.